Elmer and the dragon - Gannett, Ruth Stiles; Gannett, Ruth Chrisman (New York : Random House, 1977)
On their way home, Elmer and a flying dragon land on an unusual island and help some canaries uncover a buried treasure.
Sequel to: My Father's Dragon.
Library Journal.
4.7
3-6
Keywords: Dragons -- Juvenile fiction; Dragons -- Fiction; Dragons -- Fiction